2019
DOI: 10.7150/jca.31217
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Nivolumab in Patients with Advanced Non-small-cell Lung Cancer and Poor Performance Status

Abstract: Background: Nivolumab efficacy in patients with non-small-cell lung cancer (NSCLC) and performance status (PS) of 2-4 is unclear. We aimed to compare survival, treatment efficacy, and safety in patients with NSCLC with poor PS who received nivolumab plus best supportive care (BSC) with those in patients who received BSC alone in a palliative care unit (PCU). Patients and methods: This retrospective study included 99 consecutive patients with NSCLC who received nivolumab plus BSC or BSC alone between December 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 23 publications
2
18
0
Order By: Relevance
“…Katsura H et al studied the efficacy and safety of nivolumab among NSCLC patients with poor PS. The OS durations of patients with PS 0-1 and 2-4 were 412 and 32 days, respectively (p < 0.001) [14]. Our study is the first to focus on nivolumab for AGC patients with poor PS.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Katsura H et al studied the efficacy and safety of nivolumab among NSCLC patients with poor PS. The OS durations of patients with PS 0-1 and 2-4 were 412 and 32 days, respectively (p < 0.001) [14]. Our study is the first to focus on nivolumab for AGC patients with poor PS.…”
Section: Discussionmentioning
confidence: 69%
“…In a previous study of NSCLC (CheckMate 153 trial), irAEs were similar for the overall population (6%) and patients with an ECOG PS of 2 (9%) [11]. Katsura H et al reported that the incidence of pneumonitis in the group with poor PS was significantly higher than that in the group with good PS (35% vs. 9%, p = 0.028) [14]. Fujimoto D et al reported that the incidence rates of severe irAEs were similar between those with good PS scores (0-1) and poor PS scores (2-4) within 2 months after commencing nivolumab therapy (6.1% vs. 6.3%, respectively; p = 0.918).…”
Section: Discussionmentioning
confidence: 84%
“…Although, there were few studies of nivolumab in patients with poor PS. were 412 and 32 days, respectively (p < 0.001) [11]. Our study is the first to focus on nivolumab for AGC patients with poor PS.…”
Section: Safetymentioning
confidence: 68%
“…In a previous study of NSCLC (CheckMate 153 trial), irAEs were similar for the overall population (6%) and patients with an ECOG PS of 2 (9%) [8]. Katsura H et al reported that the incidence of pneumonitis in the group with poor PS was significantly higher than that in the group with good PS (35% vs. 9%, p = 0.028) [11]. Fujimoto D et al reported that the incidence rates of severe irAEs were similar between those with good PS scores (0-1) and poor PS scores (2-4) within 2 months after commencing nivolumab therapy (6.1% vs. 6.3%, respectively; p = 0.918).…”
Section: Safetymentioning
confidence: 84%
See 1 more Smart Citation